(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article provides a scientific-theoretical and practical analysis of pedagogical and organizational factors in the development of innovative activity within the education system. It also examines organizational factors that influence the effective implementation of innovative activities in educational institutions, including the importance of strategic planning, institutional support, motivation systems, and cooperation mechanisms. The results of the study contribute to the development of scientific and practical recommendations for modernizing the education system and improving innovative management.